Development of colour-producing β-keratin nanostructures in avian feather barbs - Prum, Richard O. (The Royal Society, 2009)
The non-iridescent structural colours of avian feather barbs are produced by coherent light scattering from amorphous (i.e. quasi-ordered) nanostructures of β-keratin and air in the medullary cells of feather barb rami. Known barb nanostructures belong to two distinct morphological classes. ‘Channel’ nanostructures consist of β-keratin bars and air channels of elongate, tortuous and twisting forms. ‘Spherical’ nanostructures consist of highly spherical air cavities that are surrounded by thin β-keratin bars and sometimes interconnected by tiny passages. Using transmission electron microscopy, we observe that the colour-producing channel-type nanostructures of medullary β-keratin in feathers of the blue-and-yellow macaw (Ara ararauna, Psittacidae) develop by intracellular self-assembly; the process proceeds in the absence of any biological prepattern created by the cell membrane, endoplasmic reticulum or cellular intermediate filaments. We examine the hypothesis that the shape and size of these self-assembled, intracellular nanostructures are determined by phase separation of β-keratin protein from the cytoplasm of the cell. The shapes of a broad sample of colour-producing channel-type nanostructures from nine avian species are very similar to those self-assembled during the phase separation of an unstable mixture, a process called spinodal decomposition (SD). In contrast, the shapes of a sample of spherical-type nanostructures from feather barbs of six species show a poor match to SD. However, spherical nanostructures show a strong morphological similarity to morphologies produced by phase separation of a metastable mixture, called nucleation and growth. We propose that colour-producing, intracellular, spongy medullary β-keratin nanostructures develop their characteristic sizes and shapes by phase separation during protein polymerization. We discuss the possible role of capillary flow through drying of medullary cells in the development of the hollow morphology of typical and spongy feather medullary cells.